DESCRIPTION OF URIC ACID LEVELS IN ELDERLY USING POINT OF CARE TESTING (POCT) METHOD IN PUSKESMAS KOTA UTARA - Batiti, Merli; Dunggio, Titin; Naim, Muh. Rizman (LPPM Universitas Bina Mandiri Gorontalo, 2024)
Uric acid is the end product of purine metabolism in the form of nucleoprotein, which is a component of nucleic acids found in the nuclei of body cells. Someone will be said to suffer from gout if the examination results show uric acid levels above 7 mg/dl for men while more than 6 mg/dl for women. In general, this uric acid disease will attack the elderly. Elderly is aged > 60 years and over. Normally have experienced various setbacks of physical abilities, as well as physiology. In the elderly, physical endurance has decreased, it is vulnerable to old age, physical endurance is getting weaker and worse. This study aims to find out and determine the description of uric acid levels in the elderly using the point care of testing (POCT) method at the North City Health Center, Gorontalo City. The method in descriptive research uses a quantitative approach and the sampling method used in this study is purposive sampling with certain criteria or considerations in taking samples. From the results of the research conducted from 14 to 23 November 2022 it showed that examination of uric acid levels at the North City Health Center on 31 samples obtained normal results in 13 samples (49.9%) and abnormal results in 18 samples (58.1%) ), while there were 16 women (51.6%) and 15 men (48.4%).